Pengembangan Media Pembelajaran Interaktif pada Proses Pembelajaran Keselamatan dan Kesehatan Kerja - Revin Rozi Pratama; Hambali Hambali (Jurnal Pendidikan Teknik Elektro, 2020)
This research is motivated by the lack of attention of students in following the learning process. This is because the learning media used do not cause direct interaction with students. As a result, not all students are serious about participating in learning activities. Therefore, interactive learning media are needed so that there is a direct interaction between students and the media used. The learning media used is the Interactive Microsoft Office Powerpoint. The purpose of this research is to produce interactive learning media that are valid, practical, and effective. The type of research used is research and development R&D (Research Development). The research model used is the ADDIE model, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The subject of this research is learning media using the Powerpoint application. Respondents of this study were 48 lecturers of K3 and Labor Law and 1LB grade students of the Department of Electrical Engineering. The results of media validation by the validator team were declared valid with an average of 0.83. The results of the practicality of the media from the lecturers of the course were 89.58% in the very practical category and from the students was 85.66% including the practical category. In the effectiveness test of the Post-test, it was found that students' classical completeness was 87.50%. So it can be concluded that this learning media is valid, practical, and effective in the learning process.